Program bimbingan kesadaran tanggung jawab sosial santri baru tingkat SMP - Naqiawardah, Nadya; Mujahdin, Endin (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
New santri in pesantren often face challenges such as difficulty adapting to the environment, lack of motivation to learn, and adjusting to rules, routines, and social interactions. This study aims to analyze, design, and test the feasibility of a social responsibility awareness guidance program for new junior high school students. The research used the Research and Development (R&D) method with the ADDIE model. The results of the analysis show that 100% of new santri experience adaptation problems, 90% do not understand their responsibilities, while only 60% of pesantren have related guidance programs. The program is systematically arranged based on Permendikbud No. 111 of 2014 with social responsibility awareness material according to Abdus Salam Zahran's theory, including the rights of Allah SWT, the rights of self, and the rights of others (environment). Validation from experts in Islamic religious education, Indonesian language, and counseling guidance showed an average feasibility of 93% with the category “Very Feasible”. Meanwhile, the assessment of pesantren practitioners resulted in an average of 86% with the same category. These results prove that the social responsibility awareness guidance program for new junior high school students is very feasible to implement as a solution to help students adapt and form responsible religious characters. Abstrak Santri baru di pesantren sering menghadapi tantangan seperti kesulitan beradaptasi dengan lingkungan, kurangnya motivasi belajar, serta menyesuaikan diri dengan tata tertib, rutinitas, dan interaksi sosial. Penelitian ini bertujuan untuk menganalisis, merancang, dan menguji kelayakan program bimbingan kesadaran tanggung jawab sosial bagi santri baru tingkat SMP. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE. Hasil analisis menunjukkan 100% santri baru mengalami masalah adaptasi, 90% belum memahami tanggung jawab mereka, sementara hanya 60% pesantren yang memiliki program bimbingan terkait. Program disusun secara sistematis berdasarkan Permendikbud No. 111 Tahun 2014 dengan materi kesadaran tanggung jawab sosial menurut teori Abdus Salam Zahran, mencakup hak Allah Swt., hak diri, dan hak orang lain (lingkungan). Validasi dari ahli pendidikan agama Islam, bahasa Indonesia, serta bimbingan konseling menunjukkan rata-rata kelayakan 93% dengan kategori “Sangat Layak”. Sementara itu, penilaian praktisi pesantren menghasilkan rata-rata 86% dengan kategori yang sama. Hasil ini membuktikan bahwa program bimbingan kesadaran tanggung jawab sosial santri baru tingkat SMP sangat layak diterapkan sebagai solusi untuk membantu santri beradaptasi dan membentuk karakter religius yang bertanggung jawab.